Assessing the level of spatial equity of public parks in Lucena City - Salonga, Jo Marice R. (School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Public parks are deemed as important components of sustainable communities, and this particular notion had been consistently communicated by scholars and policy makers through various literatures across the globe. In the aim of furthering this concept and operationalizing various standards and metrics in the Philippine setting, this research was undertaken to focus on measuring spatial equity of public parks in Lucena City, a highly urbanized city in CALABARZON region, using three most commonly applied measurements of equity namely accessibility, distribution, and quality and assessing their relationship to household income groups. The researcher used mixed- methods combining spatial analysis through the use of ArcGIS in determining the level of accessibility and distribution and conducted surveys among parkgoers in determining the level of quality. The results of the three measurements were then processed to evaluate their relationship among the income classes through Spearman's Rank Correlation and Kruskal-Wallis Test. The findings revealed that the overall condition of public parks falls under the classification of common and the level of spatial equity in the city is non-equitable, where lower income classes do not have better accessibility, distribution, and quality in reference to public parks. In response to this, the actions of the city to address the existing level of spatial equity can be summed up into two meaningful government interventions: development and maintenance of public parks, and encouragement of development of private-owned public parks. Keywords : spatial equity and public parks, geospatial analysis, income level, urban planning, Lucena City